2018
DOI: 10.2147/opth.s170552
|View full text |Cite
|
Sign up to set email alerts
|

Development of a highly sensitive and reliable enzyme-linked immunosorbent assay for MUC5AC in human tears extracted from Schirmer strips

Abstract: PurposeReliable measurement of MUC5AC in human tears is essential for elucidation of the pathophysiological role of MUC5AC in dry eye disease. The purpose of this study was to develop a sensitive and reliable method for measurement of MUC5AC in human tear samples extracted from Schirmer strips by modifying a commercially available ELISA.MethodsMUC5AC was extracted from Schirmer strips containing human tears by PBS with various concentrations of polysorbate 20. The extracts were treated with neuraminidase A to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…The MUC5AC protein in the tear lm was quanti ed using an enzyme-linked immunoassay assay (ELISA) according to a previously reported method [14]. Tears were collected using unmarked Schirmer strips (Jin Ming, Tianjin, China) and frozen at − 80°C after the length of the strip wetting with tears was measured before the next step.…”
Section: Muc5ac Measurement In Human Tear Samplesmentioning
confidence: 99%
“…The MUC5AC protein in the tear lm was quanti ed using an enzyme-linked immunoassay assay (ELISA) according to a previously reported method [14]. Tears were collected using unmarked Schirmer strips (Jin Ming, Tianjin, China) and frozen at − 80°C after the length of the strip wetting with tears was measured before the next step.…”
Section: Muc5ac Measurement In Human Tear Samplesmentioning
confidence: 99%
“…In the absence of NHE8, the tear volume is reduced by approximately 34%, along with increased focal inflammatory infiltration and foamy vacuoles within acinar cells in the lacrimal gland [7]. The conjunctival epithelial layer may also contribute to the reduction of tear volume since abnormal expression of small proline-rich protein 2H (Sprr2h) and transglutaminase 1 (Tgm1) were detected in the eyes of NHE8KO mice [97]. MUC5AC, primarily secreted mucin involved in the lubrication of the ocular surface, is produced by the goblet cells in the conjunctiva [97].…”
Section: Nhe8 Expression In the Eyesmentioning
confidence: 99%
“…The conjunctival epithelial layer may also contribute to the reduction of tear volume since abnormal expression of small proline-rich protein 2H (Sprr2h) and transglutaminase 1 (Tgm1) were detected in the eyes of NHE8KO mice [97]. MUC5AC, primarily secreted mucin involved in the lubrication of the ocular surface, is produced by the goblet cells in the conjunctiva [97]. In the absence of NHE8, the expression of Muc5ac is reduced by 60%, suggesting a role of NHE8 in goblet cell function in the eye [97].…”
Section: Nhe8 Expression In the Eyesmentioning
confidence: 99%
See 1 more Smart Citation
“…Firstly, it was recently shown that the method of collection of tear samples (microcapillary, Schirmer strips, etc.) may result in very different amount of mucins, lipids, and other compounds in the specimen which considering the complex hetero-molecular interactions behind the non-Newtonian behavior of human tears may grossly impact the sample's performance and composition [24,25]. Secondly, the commercial mucin preparations used in the experiments of Tiffany (primarily bovine submaxillary mucin) have very different levels of N-and O-glycosylation compared to ocular mucins [6,7] which certainly will affect their hydrogen bonding pattern and rheological properties.…”
Section: Number Of Hydrodynamic Models (See Equations (mentioning
confidence: 99%